Does the Implementation of the Village Financial System (Siskeudes) Program Improve the Quality of Financial Reports and Village Government Performance? - Ariyanti, Amin; Alfatih, Andy (HM Publisher, 2018)
ABSTRACT The purpose of this study was to determine the effect of the implementation of the village financial system program (Siskeudes) through the quality of financial reports on the performance of village governments in Batang District. This research is a quantitative study using a survey approach that is by distributing questionnaires. The populations in this study were all villages in Batang Regency. Sample total was 150 villages, consisting of 2 stakeholders (village heads as budget users and village treasurers as financial staff) was selected as respondents in this study. The technique used to determine the sample is cluster random sampling. The method used to analyze data is Structural Equation Modeling. The results found that the implementation of the village financial system (Siskeudes) program through the quality of financial reports significantly affected the performance of village governments in Batang District. This study recommends that financial management training involve all PTPKD (Village Financial Management Technical Tools). The need for a village government budget team (TPAP district) at the sub-district level has the task of preparing and implementing policies in the context of drafting APB district, thus accelerating the planning and budgeting stages of village finances. In addition, regular supervision needs to be intensified, namely with an online monitoring system, and the existence of a reward and punishment scheme so as to improve the performance of the village government.